'And I Hereby Declare the Runner‐Up to be the Winner': The Extraordinary 2021 DUP Leadership Election. Issue 3 (13th July 2021) - Tonge, Jonathan
Abstract: The first‐ever election for the leader of the Democratic Unionist Party (DUP) in May 2021 proved eventful in terms of both its instigation and outcome. Founded in 1971, the DUP's three previous leaders had either been self‐appointed (Ian Paisley, the party's founder) or nominated without a rival opponent (Peter Robinson and Arlene Foster). Foster's unseating in an internal coup triggered a contest between Northern Ireland Executive minister Edwin Poots and Westminster MP Sir Jeffrey Donaldson. The outcome was determined by one of the smallest selectorates of any party in the UK or Ireland, twenty‐eight DUP members of the Northern Ireland Assembly (MLAs) and the party's eight Westminster MPs. They voted narrowly to elect Edwin Poots as their new party leader. Yet, Poots lasted merely twenty‐one days in the job, replaced by Donaldson, who was unopposed when the leadership vacancy re‐arose. This article analyses an extraordinary saga.